Two minutes over Baghdad - Perlmutter, Amos (Frank Cass, 2003)
A detailed account of the way Israel dealt with the Iraqi nuclear buildup between its launch in 1974 and the destruction of the Tamuz I reactor on 7 June 1981. This updated account includes formerly classified information and photographs taken during the mission and from US spy satellites.